PENGEMBANGAN MEDIA PEMBELAJARAN QUIZ GAME DENGAN FILTERS INSTAGRAM STORY BERBASIS AUGMENTED REALITY SEBAGAI ALTERNATIF MOTIVASI PEMBELAJARAN INFORMATIKA SISWA KELAS X MPLB DI SMK IPIEMS SURABAYA - Achmad Reza Johan Maulana; Siti Sri Wulandari; Meylia Elizabeth Ranu; Novi Trisnawati (PT. Hasba Edukasi Mandiri, 2025)
learning media and determine the feasibility of the Quiz Game Learning Media with Instagram Story Filters based on Augmented Reality as an alternative to motivating Information Technology learning. It also seeks to ascertain students' motivational response in class X MPLB at SMK IPIEMS Surabaya. The type of research used is Research and Development (R&D), which adapts the development model by Reiser and Molenda, namely the ADDIE development model. There are five stages in developing this learning media: the analysis stage, the design stage, the development stage, the implementation stage, and the fifth stage, the evaluation stage. The trial of the Quiz Game Learning Media with Instagram Story Filters based on Augmented Reality was conducted on 20 students in class X MPLB at SMK IPIEMS Surabaya. Furthermore, it underwent a validity test by a media expert, specifically a lecturer in educational technology from a state university in Surabaya, and a content expert validity test by an Information Technology subject teacher at SMK IPIEMS Surabaya. The product feasibility results from the media expert showed a value of 92.5% (Very Feasible), while the two content experts yielded a total score of 93.75% (Very Feasible), and the student response score was 93.75% (Very Feasible). In conclusion, the trial and validation of the Quiz Game Learning Media with Instagram Story Filters based on Augmented Reality as an alternative motivation for Information Technology learning for class X MPLB students at SMK IPIEMS Surabaya are highly suitable as a tool or alternative motivational media for students in learning Information Technology subjects.